2023
DOI: 10.1002/aenm.202300260
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Energy Technology: Self‐Uninterrupted Electricity Power Harvesting from the Sun and Cold Space

Abstract: Harvesting sustainable energy from the sun and cold space to uninterruptedly generate green electricity provides a potential alternative way to solve the unfolding energy crisis and environmental issues. This emerging energy technology is seeing important progress and further advances remain challenging. Herein, the underlying principle, thermodynamic limit, and global potential of this technology are comprehensively reviewed. The recent advances of energy harvesters (solar absorbers or/and radiative coolers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Therefore, using energy collectors instead of batteries achieves a self-powered system [155]. Mechanical vibration energy is a common form of energy in the environment, which exhibits a more sustained, stable, and high-density energy than solar and thermal energy [156][157][158]. Future electronic products will have flexibility and deformability while maintaining the flexibility and deformability of their power supply, which is also very important [159,160].…”
Section: Energy Harvestermentioning
confidence: 99%
“…Therefore, using energy collectors instead of batteries achieves a self-powered system [155]. Mechanical vibration energy is a common form of energy in the environment, which exhibits a more sustained, stable, and high-density energy than solar and thermal energy [156][157][158]. Future electronic products will have flexibility and deformability while maintaining the flexibility and deformability of their power supply, which is also very important [159,160].…”
Section: Energy Harvestermentioning
confidence: 99%
“…Thermoelectric technology has facilitated both waste heat recovery and refrigeration applications due to the ability to convert directly between electricity and heat. The advances in wearable electronics have further stimulated the development of flexible thermoelectric materials (material performance is generally evaluated by zT = S 2 σ T /κ, where S , σ, T , and κ are the Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity, respectively), such as polymers and carbon nanotubes. , Particularly, single-walled carbon nanotubes (SWCNTs) have attracted much attention due to their excellent flexibility, abundant source, light weight, and low toxicity. Furthermore, SWCNTs possess high electrical conductivity and Seebeck coefficient, , both of which are essential for obtaining high thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 Previous research has revealed that the theoretical limits of harnessing energy from both thermodynamic resources far exceed those of relying on a single energy source, thus overcoming the limitations of solitary energy collection. 19 , 20 Consequently, the synergistic utilization of solar and cosmic energy is gradually emerging as a key research focus.…”
Section: Introductionmentioning
confidence: 99%